Empowering women through education and influence: An evaluation of the Indian Mahila Samakhya program - Eeshani Kandpal; Kathy Baylis; Mary P. Arends-Kuenning (Institute for the Study of Labor (IZA), 2012)
This paper shows that participation in a community-level female empowerment program in India significantly increases participants' physical mobility, political participation, and access to employment. The program provides support groups, literacy camps, adult education classes, and vocational training. We use truncation-corrected matching and instrumental variables on primary data to disentangle the program's mechanisms, separately considering its effect on women who work, and those who do not work but whose reservation wage is increased by participation. We also find significant spillover effects on non-participants relative to women in untreated districts.
urn:nbn:de:101:1-201205026130
Keywords: D13; I24; J16; O15; O17; 330; women's empowerment; community-level interventions; impact evaluation; India; Frauenpolitik; Frauenbildung; Wirkungsanalyse; Berufliche Integration; Gemeinde; Indien